2023
DOI: 10.1088/1402-4896/ace2f5
|View full text |Cite
|
Sign up to set email alerts
|

Broadband dielectric behaviour and structural characterization of PVDF/PMMA/OMMT polymer nanocomposites for promising performance nanodielectrics in flexible technology advances

Abstract: Characterization of broadband dielectric behaviour of polymer nanocomposites (PNCs) is vital for the exploration of efficient nanodielectrics as energy storage, flexible dielectric substrates, and insulators in a wide range of advanced electronic device technologies. Accordingly, herein, PNC films based on poly(vinylidene fluoride) (PVDF) and poly(methyl methacrylate) (PMMA) blend matrix (80/20 wt/wt%) dispersed with 0, 2.5, 5, and 10 wt% organo-modified montmorillonite (OMMT) nanoclay are developed by state-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Recently, a research group examined the improvement of the energy storage capability because they found that adding MMT is beneficial to the breakdown strength of PVDF nanocomposites because of the superior mechanical reinforcement effect and nanometric interfaces of clay minerals, resulting in a higher polarization, improved dielectric performance, and breakdown strength [24,185,[212][213][214]. Ghosh et al made the discovery that intercalation could occur in PVDF/clay nanocomposites without the need for chemical treatment.…”
Section: Montmorillonitementioning
confidence: 99%
“…Recently, a research group examined the improvement of the energy storage capability because they found that adding MMT is beneficial to the breakdown strength of PVDF nanocomposites because of the superior mechanical reinforcement effect and nanometric interfaces of clay minerals, resulting in a higher polarization, improved dielectric performance, and breakdown strength [24,185,[212][213][214]. Ghosh et al made the discovery that intercalation could occur in PVDF/clay nanocomposites without the need for chemical treatment.…”
Section: Montmorillonitementioning
confidence: 99%